Boosting conversion efficiency of lignite to oxygen-containing chemicals by thermal extraction and subsequent oxidative depolymerization. (15th January 2022) - Wu, Zequan; Wang, Zhicai; Wu, Tao; Li, Zhanku; Yan, Jingchong; Pan, Chunxiu; Kang, Shigang; Lei, Zhiping; Ren, Shibiao; Shui, Hengfu
Highlights: An efficient non-fuel utilizing approach of low-rank coal is obtained by TE and the oxy-cracking. TE can separate the extractables, and greatly reduce the formation of CO2 during oxy-cracking. Oxy-cracking of TER under mild conditions is dominated by the oxidative depolymerization. Oxy-cracking of TER is characterized by mild conditions, less alkali dosage and low CO2 emission. Abstract: The urgent need to reduce CO2 emission in China has stimulated renewed interest in the use of coal as raw material for chemical production. Oxidation in aqueous solution is a relatively mild method to depolymerize coal into oxygen-containing chemicals. In this paper, a novel technology combining thermal extraction (TE) of coal and the oxy-cracking of TE residue (TER), referring to the oxygen oxidation in alkaline aqueous solution under mild conditions, was proposed to obtain humic acid (HA) from Xilinguole lignite (XL). The results show that TE could not only obtain small molecular extracts, but also significantly affect the oxy-cracking performance of TER to reduce the formation of CO2 . TE yield of XL reached 9.8 % at optimized temperature (300 °C). Almost no CO2 was emitted during the oxy-cracking of obtained TER at 120 °C for 1.5 h, and the oxy-cracking conversion and the HA yield were 65.03 %and 40.56 %, respectively. By the characterizations of FTIR, 13 C NMR, XPS, etc, the HA mainly consists of aromatic structures and oxygen-containing groups, in which most of acidic groups are carboxyl groups. It has an extensive application in the production of industrial chemicals, such as admixtures of concrete, dispersant of coal water slurry, and so on. Therefore, the preparation technology of coal-based HA combining TE and TER oxy-cracking is a promising utilization approach of low-rank coal.